Therapeutic Potential and Immunomodulatory Role of Coenzyme Q10 and Its Analogues in Systemic Autoimmune Diseases - Chary López-Pedrera; José Manuel Villalba; Alejandra Mª Patiño-Trives; Maria Luque-Tévar; Nuria Barbarroja; Mª Ángeles Aguirre; Alejandro Escudero-Contreras; Carlos Pérez-Sánchez (Antioxidants, 2021)
Coenzyme Q10 (CoQ10) is a mitochondrial electron carrier and a powerful lipophilic antioxidant located in membranes and plasma lipoproteins. CoQ10 is endogenously synthesized and obtained from the diet, which has raised interest in its therapeutic potential against pathologies related to mitochondrial dysfunction and enhanced oxidative stress. Novel formulations of solubilized CoQ10 and the stabilization of reduced CoQ10 (ubiquinol) have improved its bioavailability and efficacy. Synthetic analogues with increased solubility, such as idebenone, or accumulated selectively in mitochondria, such as MitoQ, have also demonstrated promising properties. CoQ10 has shown beneficial effects in autoimmune diseases. Leukocytes from antiphospholipid syndrome (APS) patients exhibit an oxidative perturbation closely related to the prothrombotic status. In vivo ubiquinol supplementation in APS modulated the overexpression of inflammatory and thrombotic risk-markers. Mitochondrial abnormalities also contribute to immune dysregulation and organ damage in systemic lupus erythematosus (SLE). Idebenone and MitoQ improved clinical and immunological features of lupus-like disease in mice. Clinical trials and experimental models have further demonstrated a therapeutic role for CoQ10 in Rheumatoid Arthritis, multiple sclerosis and type 1 diabetes. This review summarizes the effects of CoQ10 and its analogs in modulating processes involved in autoimmune disorders, highlighting the potential of these therapeutic approaches for patients with immune-mediated diseases.